(untitled) (Fiep Bulletin - online, 2013)
A medicinal herb called mugword is burned, which produces a therapeutic Rheumatoid arthritis is an inflammatory polyarthritis with exacerbation of pain and articular volume leading to progressive deformities and even permanent disability. In Traditional Chinese Medicine rheumatoid arthritis is classified as a ’’painful obstruction syndrome’’ characterized by pain, abnormal sensibility and paresthesia due to external invasion of Cold, Wind and Humidity in a body of fragile constitution. Moxibustion is a technique of treatment used in Chinese Medicine, in which heating effect in the human body, removing meridian obstructions. The goal of this study was to determine the effects of the moxibustion technique in a subject suffering from Rheumatoid Arthritis. This is a case study where a patient diagnosed with Rheumatoid arthritis was submitted to ten sessions of moxibustion. At the beginning of each session the edema was measured and the joint pain was graded with the Visual Analogue Scale. At the initial and final sessions the patient answered questions that were used for further analysis. At the end of the treatment there was a statistically significant improvement on the joint pain and also an improvement in the day-to-day disposition. Regarding the joint edemas and the swollen joints there were no significant changes.